Hubungan Antara Komitmen Organisasi Dan Kepuasan Kerja Dengan Organizational Citizenship Behavior (OCB) Pada Perawat di Rumah Sakit Umum Wisma Rini Pringsewu - Supriyati Supriyati; Dewi Lutfianawati; Octa Reni Setiawati; Andini alfira Putri (Puslitbang Sinergis Asa Professional, 2021)
In the hospital industry, the performance of nurses is very important in the success in the hospital. It is necessary for the workforce to be able to work optimally and the role of Organizational Citizenship Behavior (OCB). OCB is a behavior of an employee that is not formally regulated and can improve the performance of the organization. Some of the factors that affect OCB are organizational commitment and job satisfaction. Therefore, this study aims to find out the relationship of organizational commitment and job satisfaction with OCB. Data collection in this study used OCB scale, organizational commitment, and job satisfaction. Sampling using total sampling, with a sample number of 100 nurses at the public hospital Wisma Rini Pringsewu. Data analysis using multiple linear regression analysis with the help of SPSS 22.0 for windows. The results showed that Deviation From Linearity between OCB and Organizational Commitment of 0.707 and between OCB and Job Satisfaction of 0.602, where the value of each variable is p>0.05s so that it indicates there is a linear relationship, and can be continued with hypothetical tests. It is known that the first hypothesis is that the relationship between organizational commitment and job satisfaction is positively correlated with ocb variables with the significance of p<0.01 and p<0.05 received. The conclusion is that there is a relationship between organizational commitment and job satisfaction with Organizational Citizenship Behavior (OCB)